Target Molecules and Delivery Vehicles for Anti-HIV Drugs In vitro and In vivo - Bolhassani, Azam (Current Pharmaceutical Design, 2018)
Acquired Immune Deficiency Syndrome (AIDS) is the most serious stage of Human Immunodeficiency Virus (HIV) infection. The combinatorial Anti-Retroviral Therapy (cART) is widely used in suppressing HIV-1 infection and enhancing life span of infected patients to a significant level. However, delivery of therapeutic molecules is still a major challenge in vivo. The studies showed that the anti-HIV drugs delivered via nanocarriers could be selectively accumulated in infected cells accompanied by low side effects. On the other hand, HIV-1 infection kinetics is different in macrophages and T-cells suggesting various effects of antiretroviral drugs against HIV-1 in these target cells. Current anti-HIV therapeutic studies have focused on developing drug delivery systems targeted specifically to HIV-infected host cells. Indeed, the drug targeting can significantly lead to reduce in drug toxicity, drug dose, and increase in treatment efficacy through localizing its pharmacological activity to the site of interest. This review describes development of novel drug targeting systems used in suppressing the transmission and treatment of HIV infections.
Keywords: adverse effects